Holocene landscape dynamics in the Ghaggar-Hakra palaeochannel region at the northern edge of the Thar Desert, northwest India - Durcan, J; Thomas, D; Gupta, S; Pawar, V; Singh, R; Petrie, C (Elsevier, 2017)
Precession-forced change in insolation has driven de-intensification of the Asian Monsoon systems during the Holocene. Set against this backdrop of a weakening monsoon, Indus Civilisation populations occupied a number of urban settlements on the Ghaggar-Hakra plains during the mid-Holocene from 4.5 ka until they were abandoned by around 3.9 ka. Regional climatic variability has long been cited as a potential factor in the transformation of Indus society, however there remain substantial gaps in the chronological framework for regional climatic and environmental change at the northern margin of the Thar Desert. This makes establishing a link between climate, environment and society challenging. This paper presents 24 optically stimulated luminescence ages from a mixture of 11 fluvial and aeolian sedimentological sites on the Ghaggar-Hakra floodplain/interfluve, an area which was apparently densely populated during the Indus urban phase and subsequently. These ages identify fluvial deposition which mostly pre-dates 5 ka, although fluvial deposits are detected in the Ghaggar palaeochannel at 3.8 ka and 3.0 ka, post-dating the decline of urbanism. Aeolian accumulation phases occur around 9 ka, 6.5 ka, 2.8 ka and 1.7 ka. There is no clear link to a 4.2 ka abrupt climate event, nor is there a simple switch between dominant fluvial deposition and aeolian accumulation, and instead the OSL ages reported present a view of a highly dynamic geomorphic system during the Holocene. The decline of Indus urbanism was not spatially or temporally instantaneous, and this paper suggests that the same can be said for the geomorphic response of the northern Thar to regional climate change.